Polityka finansowa dolnośląskich szkół wyższych w procesie transformacji - Popiński, Krzysztof (Financial Policy of Higher Schools in Lower Silesia During Transformation, 2006)
The article analyzes selected problems of financial policy of higher schools in Poland in general and a few most important schools in Lower Silesia in particular. Over the last years the financial situation of the schools has not been improving sufficiently despite a relative growth in public spending on education in Poland and in spite of the growth in income generated by the schools themselves. The reason for this are growing teaching costs, caused first of all by growing number of students. Subsidies are provided almost exclusively to state schools, whereas numerous newly-founded non-state schools - in their vast majority - have to rely on tuition fees as their only source of income. As a result the state schools, which are limited by many regulations, are less eager to carry out changes that coud lead to rationalisation of their financial policy. There is no doubt, however, that financial reform, apart from changes in the organisation and educational agenda and improvement in teachers' qualifications, should be one of the main elements of the future strategies for Polish (including those of Lower Silesia) state higher schools.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 624-638